Realities and unrealities in the hungarian child protection system from the perspective of social mobility = Realia i nierówności w węgierskim systemie ochrony dzieci z punktu widzenia mobilności społecznej - Rácz, Andrea (Zielona Góra: Lubuskie Towarzystwo Naukowe)
We have limited information about the relationship between the quality of the social and child protection system and the chances of social mobility, on how the social system can contribute to improving the well-being of the clients, and on how the system limits it with exclusionary procedures in Hungary.
Keywords: social mobility; child protection; quality of life; future developments; welfare pluralism; mobilność społeczna; ochrona dzieci; jakość życia; perspektywy rozwoju; pluralizm opieki społecznej